Gender, tenure security, and landscape governance - Jhaveri, Nayna (International Food Policy Research Institute, 2021)
Gender relations in households and communities play a formative role in how tenure rights — such as access to, use, and management of land and various natural resources — are practiced across multifunctional landscapes. Such rights can be based on statutory recognition or on customary tenure arrangements. Women’s tenure rights are generally weaker than men’s, both in terms of the range of rights they can assert and the degree of authority over those rights. In addition, women often hold a more informal and negotiated set of rights than men, be it for private or collective use of land and natural resources. These gender differences are the outcome of decision-making and governance at the household and community level. In any rural landscape in developing countries, a household’s livelihood portfolio will be affected by the gender dynamics at work across the landscape mosaic of different tenure niches. For example, women may easily access privately owned home gardens (one type of tenure niche) to harvest a range of vegetables, fruits, and medicinal plants, but not so easily access trees in collective forests for harvesting timber to sell in the market.